Dynamics of the public-debt-to-gdp ratio: Can it explain the risk premium of treasury bonds? - Lagoa, S.; Leão, E.; Bhimjee, D. (Empirica, 2022)
We examine the relationship between the risk premium markets demand to hold the Treasury Bonds of a given country and the sustainability of the public finances of the country. We inquire to what extent do markets use the dynamic evolution of the public-debt-to-gdp ratio as an indication of the likelihood of a public debt default. Specifically, our empirical research design involves the following steps: (i) we use the dynamic equation of the public-debt-to-gdp ratio to build forecasts of future values of this ratio in the eurozone countries; (ii) we then use these forecasts in a regression to see how important they are to explain the risk premium implicit in the treasury bond yields. We find that projections of future values of the public-debt-to-gdp ratio do impact current 10 year bond spreads. According to our regressions, markets seem to give more weight to forecasts with a horizon smaller than 10 years. Our results suggest that agents use a relatively simple mechanism to forecast the public debt-to-gdp ratio, a mechanism which can be used while updated forecasts from international organizations are not yet available. On the other hand, according to our estimations, euro area sovereign debt markets ceased to significantly discriminate countries based on their public debt prospects after the 2012 ‘Whatever It Takes” speech and the announcement of the Outright Monetary Transactions (OMT) program—suggesting that these events had a significant calming effect on the markets.